Improving Hankel transform filters for parallel electromagnetic modeling tools - Gruver, Y.; Puzyrev, Vladimir; De La Puente, J. (2015)
Calculation of the electromagnetic fields for a source above a layered media often requires evaluations of Hankel transforms. 3D modelling schemes that are based on the scattered field formulation require the calculation of Hankel transforms in all points of the computational domain. We show that with a parallelization and optimization of the digital filters it is possible to calculate accurate 1D solutions for each node of the grid on-the-fly. Even with the use of the high-quality filters, the computational cost is negligible compared to the subsequent solution of a 3D problem.